Cotton CC-NBS-LRR Gene GbCNL130 Confers Resistance to Verticillium Wilt Across Different Species - Li, Tinggang; Zhang, Qianqian; Jiang, Xilong; Li, Ran; Dhar, Nikhilesh (Frontiers in Plant Science, 2021)
Verticillium wilt (VW) is a destructive disease in cotton caused by Verticillium dahliae and has a significant impact on yield and quality. In the absence of safe and effective chemical control, VW is difficult to manage. Thus, at present, developing resistant varieties is the most economical and effective method of controlling Verticillium wilt of cotton. The CC-NBS-LRR (CNL) gene family is an important class of plant genes involved in disease resistance. This study identified 141 GbCNLs in Gossypium barbadense genome, with 37.5% (53 genes) GbCNLs enriched in 12 gene clusters (GC01–GC12) based on gene distribution in the chromosomes. Especially, seven GbCNLs from two largest clusters (GC11 and GC12) were significantly upregulated in the resistant cultivar (Hai No. 7124) and the susceptible (Giza No. 57). Virus-induced gene silencing of GbCNL130 in G. barbadense, one typical gene in the gene cluster 12 (GC12), significantly altered the response to VW, compromising plant resistance to V. dahliae. In contrast, GbCNL130 overexpression significantly increased the resistance to VW in the wild-type Arabidopsis thaliana. Based on our research findings presented here, we conclude that GbCNL130 promotes resistance to VW by activating the salicylic acid (SA)-dependent defense response pathway resulting in strong accumulation of reactive oxygen species and upregulation of pathogenesis-related (PR) genes. In conclusion, our study resulted in the discovery of a new CNL resistance gene in cotton, GbCNL130, that confers resistance to VW across different hosts.